Aligning Social Media Indicators with the Documents in an Open Access Repository - Meneses, Luis; Arbuckle, Alyssa; Lopez, Hector; Moa, Belaid; Furuta, Richard; Siemens, Ray (KULA, 2019)
In this paper we describe our current efforts towards building a framework that extends the functionality of an Open Access Repository by implementing processes to incorporate the ongoing trends in social media into the context of a digital collection. We refer to these processes collectively as the Social Media Engine. The purpose of our framework is twofold: first, we propose to challenge some of the preconceived notions of digital libraries by making repositories more dynamic; and second, by challenging this notion we want to promote public engagement and open scholarship. As a work in progress, we believe that a real challenge lies in investigating the implications that these two points introduce within the context of the humanities.